1991
DOI: 10.1007/bf00229222
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of growth curve parameters in chickens

Abstract: Genetic improvement in growth of poultry has traditionally proceeded via selection for body weight at a fixed age. Due to increased maintenance costs and reproductive problems of adult broiler breeders, the potential for genetic manipulation of the growth curve has been receiving increased interest. Research of both male and female progeny of a three-way diallel cross was used to investigate the inheritance of growth curve parameters. The Laird form of the Gompertz equation was used to determine growth curve p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
47
6
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 27 publications
13
47
6
4
Order By: Relevance
“…Reciprocal line crosses indicate significant sex-linked effects in many insect, bird and mammal species (Barbato, 1991;Reinhold, 1994Reinhold, , 1998Reinhold, , 2002Wolfenbarger and Wilkinson, 2001). Although maternal effects may inflate these estimates in mammals, this is less likely in birds and insects (Wolfenbarger and Wilkinson, 2001;Reinhold, 2002).…”
Section: Previous Empirical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reciprocal line crosses indicate significant sex-linked effects in many insect, bird and mammal species (Barbato, 1991;Reinhold, 1994Reinhold, , 1998Reinhold, , 2002Wolfenbarger and Wilkinson, 2001). Although maternal effects may inflate these estimates in mammals, this is less likely in birds and insects (Wolfenbarger and Wilkinson, 2001;Reinhold, 2002).…”
Section: Previous Empirical Testsmentioning
confidence: 99%
“…Model fitting is hierarchical, beginning with a simple model, such as the additive model (i.e., the expected mean phenotype of the crosses is a simple linear function of the relative contributions of the parental genomes such that the mean population values of the different crosses fall on a line connecting the two parental means, top graph, Figure 2), and increasing its complexity only if the model fails the joint-scaling test. In the presence of sex-linked effects, the expected mean phenotypic values change (Figure 2), and the line-cross analysis can be expanded to estimate sex-linked, epistatic and maternal effects (e.g., Carbonell et al, 1985;Barbato, 1991;Barbato and Vasilatos-Younken, 1991;Polak and Starmer, 2001;Huttunen and Aspi, 2003).…”
Section: Experimental Protocols: Using Crosses Between Populations Tomentioning
confidence: 99%
“…Perhaps the initial growth rate allows them to develop wing span necessary for such high thrust flights, but underdeveloped keel could be responsible for their short duration. Similar to most avian species (Barbato, 1991;Aggrey, 2002), the correlation between the L and K growth parameters are high (r = 0.92-0.96).…”
Section: Resultsmentioning
confidence: 72%
“…Prediction of growth patterns has been studied extensively in other avian species, especially domestic fowl (Grossman and Bohren, 1982;Barbato, 1991;Aggrey, 2002;Aggrey, 2004). Growth comprises of hyperplasia, hypertrophy, cell division and apoptosis, however, these processes can also be affected by environmental fluctuations, dietary status, diseases and other by random events causing growth to fluctuate thereby making the study at a single point unattractive.…”
Section: Introductionmentioning
confidence: 99%
“…Both A, the asymptotic adult weight, and k the maturing index, could be considered since each has a clear biological meaning. Although negative genetic correlation is usually expected between parameters A and k (Notter et al, 1990;Barbato, 1991;Santoro et al, 2005), positive genetic correlation has been found for Nelore, polled Nelore and Guzerá cattle when logistic, von Bertalanffy and Richards growth curves are used (Santoro et al, 2005;Forni, 2007;Forni et al, 2007). In this work we focussed attention on the parameter A. Sire selection based on this parameter has in mind an increasing of the overall weight (or of the growth rate) up to the age in which information are available (around 2.5 years in this work).…”
Section: Resultsmentioning
confidence: 99%